2018
DOI: 10.1007/s00702-018-1847-7
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in l-DOPA-induced dyskinesia: from receptor sensitization to abnormal gene expression

Abstract: A large number of signaling abnormalities have been implicated in the emergence and expression of l-DOPA-induced dyskinesia (LID). The primary cause for many of these changes is the development of sensitization at dopamine receptors located on striatal projection neurons (SPN). This initial priming, which is particularly evident at the level of dopamine D1 receptors (D1R), can be viewed as a homeostatic response to dopamine depletion and is further exacerbated by chronic administration of l-DOPA, through a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 160 publications
(244 reference statements)
0
37
0
1
Order By: Relevance
“…Postsynaptic changes include a variety of structural and molecular adaptations in striatal projection neurons (medium spiny neurons, MSNs), following dopamine denervation and L-DOPA treatment [ 20 , 21 ]. These neuronal changes comprise “supersensitive” postsynaptic (D1) dopamine receptors in the direct pathway (striatonigral) MSNs (dMSNs) [ 22 , 23 , 24 ], which, in the presence of supraphysiological dopamine levels, produce aberrant second messenger signaling [ 9 , 24 , 25 ], resulting in facilitated neuronal activity (e.g., [ 26 ]) and enhanced transmitter release (e.g., [ 13 , 27 ]), as well as dysregulated gene expression [ 8 , 9 ] in these neurons. Studies have shown that L-DOPA treatment after dopamine lesions produces changes in the regulation of thousands of genes in MSNs (e.g., [ 9 , 28 , 29 , 30 ]), including those encoding various neuropeptides, receptors, and transcription factors, and several of these have been directly related to the occurrence or severity of L-DOPA-induced dyskinesia (e.g., [ 31 , 32 , 33 , 34 ]; [ 9 ], for review).…”
Section: Introductionmentioning
confidence: 99%
“…Postsynaptic changes include a variety of structural and molecular adaptations in striatal projection neurons (medium spiny neurons, MSNs), following dopamine denervation and L-DOPA treatment [ 20 , 21 ]. These neuronal changes comprise “supersensitive” postsynaptic (D1) dopamine receptors in the direct pathway (striatonigral) MSNs (dMSNs) [ 22 , 23 , 24 ], which, in the presence of supraphysiological dopamine levels, produce aberrant second messenger signaling [ 9 , 24 , 25 ], resulting in facilitated neuronal activity (e.g., [ 26 ]) and enhanced transmitter release (e.g., [ 13 , 27 ]), as well as dysregulated gene expression [ 8 , 9 ] in these neurons. Studies have shown that L-DOPA treatment after dopamine lesions produces changes in the regulation of thousands of genes in MSNs (e.g., [ 9 , 28 , 29 , 30 ]), including those encoding various neuropeptides, receptors, and transcription factors, and several of these have been directly related to the occurrence or severity of L-DOPA-induced dyskinesia (e.g., [ 31 , 32 , 33 , 34 ]; [ 9 ], for review).…”
Section: Introductionmentioning
confidence: 99%
“…A chronic regimen of L-DOPA/benserazide that induced dyskinesia also resulted in attenuation of this enhanced signalling, even though D1R-associated dyskinesia was significantly increased. The occurrence of D1R supersensitivity is well established in 6-OHDA lesioned rats [reviewed in 50,51 ], and a recent study using FRET-based biosensors has demonstrated hyperactivation of PKA and ERK1/2 by D1R agonists in striatal slices taken from 6-OHDA lesioned mice 52 . The present in vivo study extends these ex vivo findings, by showing that acute D1R-induced PKA and ERK1/2 activation is suppressed by repeated L-DOPA treatment, suggesting that while D1R signalling may be desensitized by chronic L-DOPA treatment, the D1R-driven dyskinesia nevertheless increases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia is associated with the activation of ERK ( 61 ). Dabrafenib also activates ERK in cells with wild-type BRAF and thus may potentially exacerbate dyskinesia.…”
Section: Discussionmentioning
confidence: 99%